Net Working Capital and Firm Performance: The Moderating Role of Firm Size in Emerging Markets - Thuy Thi Cam Nguyen (Emerging Science Journal, 2026)
This study examines the relationship between net working capital and business performance and analyzes the moderating role of firm size in this relationship in emerging markets. Drawing on trade-off theory, the resource-based perspective, and agency theory, the study suggests that the impact of net working capital on performance varies with firm size. Using panel data on 370 non-financial publicly traded companies in Vietnam from 2013 to 2024, the study employs an interaction regression model with firm size as the moderating variable. The analysis proceeds in multiple steps, including OLS, fixed-effects, random-effects, and FGLS models, and, in particular, a GMM-robust model to address endogeneity, heteroskedasticity, and autocorrelation. Empirical results show that net working capital significantly affects business performance, as measured by ROA and ROE. Firm size not only directly affects operational efficiency but also moderates the relationship between net working capital and operational efficiency. Specifically, the impact of net working capital differs significantly across firm sizes, reflecting differences in resource access and management efficiency. This research contributes to the existing literature by clarifying the moderating mechanism of firm size in working capital management and by providing new empirical evidence from emerging markets, offering important implications for managers and policymakers.